2017
DOI: 10.19150/me.7567
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a mine fire using atmospheric monitoring system sensor data

Abstract: Atmospheric monitoring systems (AMS) have been widely used in underground coal mines in the United States for the detection of fire in the belt entry and the monitoring of other ventilation-related parameters such as airflow velocity and methane concentration in specific mine locations. In addition to an AMS being able to detect a mine fire, the AMS data have the potential to provide fire characteristic information such as fire growth — in terms of heat release rate — and exact fire location. Such information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…The timing of the reduction of CO gas is important to consider during blasting in the development tunnel because if CO gas does not dissipate when workers re-enter for work, it can cause poisoning [9]. To meet the needs of air and heat flow and to dilute toxic gases in underground mines, careful calculations are required for the placement of ventilation ducts, fan speed, and good air circulation conditions, ensuring that fresh air and heat can circulate properly, thereby creating a safe and comfortable working environment [10]. The purpose of this research is to study how quickly CO gas dissipates at the observation distance used.…”
Section: Introductionmentioning
confidence: 99%
“…The timing of the reduction of CO gas is important to consider during blasting in the development tunnel because if CO gas does not dissipate when workers re-enter for work, it can cause poisoning [9]. To meet the needs of air and heat flow and to dilute toxic gases in underground mines, careful calculations are required for the placement of ventilation ducts, fan speed, and good air circulation conditions, ensuring that fresh air and heat can circulate properly, thereby creating a safe and comfortable working environment [10]. The purpose of this research is to study how quickly CO gas dissipates at the observation distance used.…”
Section: Introductionmentioning
confidence: 99%
“…He combined various sensitivity and correlation evaluation indicators to monitor and analyze transportation carbon emissions. Yuan et al (2017) research showed that AMS monitors airflow velocity and methane concentration among other ventilation-related parameters at specific mine locations. Based on the theory of heat and mass transfer in ventilation airflow, it uses CO, CO, and airflow velocity from AMS sensor data.…”
Section: Introductionmentioning
confidence: 99%